2009
DOI: 10.1111/j.1751-1097.2009.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

MC1R Gene Polymorphism Affects Skin Color and Phenotypic Features Related to Sun Sensitivity in a Population of French Adult Women

Abstract: The melanocortin-1 receptor (MC1R) gene is known to play a major role in skin and hair pigmentation and to be highly polymorphic in Caucasians. This study was performed to investigate the relationships between MC1R gene polymorphisms and skin color in a large sample of French middle-aged Caucasian women. The codons 60 to 265 and the codon 294 of the MC1R gene were sequenced in 488 women. The skin color was measured on the inner side of the forearm using a spectrophotometric instrument. Fifteen variants were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
2
15
1
1
Order By: Relevance
“…However, our findings show an absence of a significant effect of the r variants on sunlight sensitivity. These results are consistent with those reported by Latreille et al, which found that r variants were significantly associated with freckling (usually a signal of high sensitivity to sunlight) but not with sunburn event frequency nor suntan intensity.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, our findings show an absence of a significant effect of the r variants on sunlight sensitivity. These results are consistent with those reported by Latreille et al, which found that r variants were significantly associated with freckling (usually a signal of high sensitivity to sunlight) but not with sunburn event frequency nor suntan intensity.…”
Section: Discussionsupporting
confidence: 93%
“…Among all nonsynonymous MC1R variants described, R variants have been the most frequently associated with fair skin, red hair, freckling and poor tanning ability —all phenotypes increasing the risk of developing skin cancer. As expected, in this study, individuals carrying R variants in MC1R present a significantly higher risk of sunburn after sunlight exposure, confirming the impact of MC1R gene polymorphism on tanning ability and the risk of sunburn shown in previous population‐based studies . However, our findings show an absence of a significant effect of the r variants on sunlight sensitivity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A study in the UK and Ireland showed that the identification of a dosage effect of MC1R variant alleles on sensitivity to UVR, and the large attributable risk for heterozygotes, suggests that the MC1R gene is closely associated with variation in the skin’s response to UVR in most of the population who do not have red hair (40). Also, associations between MC1R polymorphisms and the risks of experiencing sunburn and of having freckles were found independently of skin color, suggesting that MC1R polymorphisms do not necessarily alter the skin color, but can sensitize the skin to UV‐induced DNA damage (70).…”
Section: Phenotypic Expression Of Distinct Mc1r Variantsmentioning
confidence: 99%
“…Nous avons montré précédemment que ces variants étaient également associés aux caractéristiques phénotypiques liées au phototype [17,18]. En effet, ces variants du MC1R sont responsables d'une diminution de la synthèse d'eumélanine au profit de la phaeomélanine.…”
Section: Discussionunclassified